20-Years Cumulative Impact From Shrimp Farming on Mangroves of Northeast Brazil - de Lacerda, Luiz Drude; Ward, Raymond D.; Godoy, Mario Duarte Pinto; de Andrade Meireles, Antônio Jeovah; Borges, Rebecca; Ferreira, Alexander Cesar (Frontiers in Forests and Global Change, 2021)
Brazilian mangroves cover 1.0 - 1.4 million hectares, provide a wide range of ecosystem services and yet are one of the most impacted ecosystems as a result of combined influences of climate change, pollution, and direct conversion and loss. A major driver of environmental impacts is shrimp farming and this is particularly acute in the semi-arid northeast of Brazil, where mangroves are constrained in a narrow band along ephemeral estuaries that are often impacted by multi-year droughts. Recent changes to Brazilian law, in particular the Forest Code, have weakened protections for mangroves and in particular associated ‘apicuns’ (salt pan) ecosystems. In the northeast of Brazil, most shrimp ponds are converted from mangrove adjacent ‘apicuns’ rather than the mangroves themselves with periodic hydrological connectivity through dammed channels, allowing the flushing of effluents to the mangroves. As a result, the main impacts on mangroves are typically indirect, as a result of pollution inputs from shrimp pond effluents and associated loss of ecosystem services including reductions in: primary productivity, carbon storage, resilience to other environmental stressors, the efficiency of the estuarine filter, and biodiversity and abundance of subsistence use marine species. Soil damage and infrastructure remaining after shrimp pond deactivation impairs mangrove recovery. This extends the duration of the damage and allows the occupation of degraded areas by other activities that can permanently impair ecosystem function. In this review, we address several aspects of the shrimp culture boom in the Brazilian northeast region, their features and consequences, and future of mangroves in the region in light of climate change and rising poverty.